United Kingdom : Financial Sector Assessment Program-Select Issues in Financial Safety Net Arrangements and Financial Crisis Preparedness. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The United Kingdom (U.K.) bank resolution and financial crisis readiness arrangements are sound but with opportunities for continued and accelerated enhancements. The U.K. authorities' individual and collective crisis readiness-including with other major jurisdictions-continues to improve. Mid-2022, all major U.K. banks and the authorities will issue the first public statements about these banks' resolvability. This is supported by a comprehensive special resolution regime (SRR) and resolvability assessment framework (RAF) for banks. Yet, there is space-and a need-to further enhance the SRR, including its application to central counterparties (CCPs), and to introduce one for insurance companies. Furthermore, elements of the deposit insurance system and firm-specific resolution decision-making should be strengthened, and implementation and reputation risk addressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy